FINANCIAL TOXICITY: AN EMERGING PROBLEM FOR CANCER PATIENTS - Francesco Perrone (Journal of Cancer Rehabilitation)
Financial toxicity is one of the emerging problems in the management of cancer patients, mainly in countries characterized by a private health system and in those defned as low-middle income countries (LMIC). However, data published in 2016 have shown that it is also a problem in Italy.